KAJIAN KINERJA SIMPANG DI KOTA RAHA (STUDI KASUS SIMPANG POLSEK KATOBU) - Wulandari , Anastasia; Basri, Lambang; Alifuddin, Andi (Journal of Scientech Research and Development, 2023)
The aim of this research is to analyze the performance of the Katobu police intersection in Raha City and examine the comparison of the level of service at the intersection when it does not use a traffic light compared to the presence of a traffic light. The data collection stage, namely by calculating the volume of vehicles passing through the Katobu Police Station intersection, was carried out for 1 day without a traffic light and 3 days with a traffic light to determine the amount of flow and then recording the geometric data of the Katobu Police Station intersection for input data requirements in the 1997 MKJI calculation. Based on the results of research at the Katobu Police intersection, it was found that the performance of the Katobu Police intersection seen from the peak hour volume without a traffic light on Friday at 15.45 - 16-45 WITA was 2657 pcu/hour, while the peak hour volume with the presence of a traffic light was on Monday at 07.45 – 08.45 WITA amounting to 1616 pcu/hour. The degree of saturation without traffic lights on the North approach is 1.26 and the South approach is 1.32, the East approach is 1.03 and the West approach is 0.94. Meanwhile, the degree of saturation with traffic lights on the North approach is 0.55 and the South approach is 0.52, the East approach is 0.82 and the West approach is 0.64. According to MKJI (1997), from the value of the degree of saturation without a traffic light, the intersection condition is still very bad and unstable, whereas with the presence of a traffic light, the intersection condition is quite stable. The level of service obtained at the Katobu Police intersection without a traffic light is classified as service level "F", while with the presence of a traffic light it is categorized as service level "C", so it can be concluded that the condition of the Katobu Police intersection with a traffic light is getting better.